Environmental taxes in the long run - Henrik Vetter (Kiel Institute for the World Economy (IfW), 2013)
The efficiency of the Pigouvian tax suggests that price-based regulation is the proper benchmark for efficient regulation. However, results due to Carlton and Loury (1980, 1986) question this; when harm depends on scale effects a pure Pigou tax is inefficient regulation in the long run. In this note we make precise that there is an efficient tax scheme for controlling harm as long as social optimum exists. In particular, the efficient tax scheme is based on a tax rate equal to marginal harm. Hence, price regulation is the right benchmark for regulation even in the presence of scale effects in the harm function.
Keywords: D61; D62; 330; externalities; scale effects; Pigou-taxes